Dato Michael Tio and PKT logistics— A knowledge creating service company growing into a global logistics company - Belal, H. M.; Hasan, Quamrul; Nordin, Norani; Kosaka, Michitaka (Springer, 2019)
We introduce PKT Logistics Group Sdn Bhd. (PKT) and its CEO: Dato’ Michael B. Y. Tio (DMT) as a successful Malaysian knowledge creating service company. We examine how PKT designed and adapted the knowledge-creating system into their company’s philosophy towards business operation, thereby innovating service and acquiring more of the global market. This chapter is structured as follows: reviewing the background and the outline of PKT Logistics, introducing DMT’s entrepreneurship and policies in the development of PKT, DMT’s leadership, examining the Facebook community as a success factor for a knowledge creating service company, the future vision of PKT, the analysis of DMT’s entrepreneurship and briefly summarizing.